Pengaruh Pengelolaan Keuangan Daerah Dan Good Governance Terhadap Kinerja Pemerintah Daerah Kabupaten Kerinci - Maryanto (LP2M Politeknik Jambi, 2020)
This study aims to determine the Effect of Regional Financial Management and Good Governance on Government Performance in Kerinci Regency simultaneously and partially. The population of this study is employees at the Kerinci Regency, using the sampling technique that is purposive sampling. Respondents in the study are from the parts or devices related to this study. The number of respondents in this study amounted to 75 respondents. Data was collected by a questionnaire that had been tested for validity and reliability.The data analysis technique used is multiple regression. The results of the study show that Regional Financial Management has an effect on Government Performance in Kerinci Regency, this is evidenced by t count > t table (3.670 > 1,99346). Good Governance has an effect on Government Performance in Kerinci Regency, this is proved by t count > t table (6,072 > 1,99346). Simultaneously there is a significant influence between Regional Financial Management and Good Governance on Government Performance in Kerinci Regency that can be proven by F count > F table (37,508 > 3,12). The magnitude of the influence of Regional Financial Management and Good Governance on Government Performance in Kerinci Regency was 51%. While the remaining 49% is explained by other causes that were not examined in this study.